A simple preparation of Co0.75Fe0.25 hydrous oxide nanoparticles as active electrocatalysts for water oxidation reaction. (7th May 2020) - Wang, Chao; Chai, Le; Tian, Qianhong; Liu, Shuling
Summary: A serious of CoFe hydrous oxide nanoparticles (Co1−z Fez Ox Hy NP [z = 0‐1]) were synthesized by stirring CoCl2 and FeCl2 in aqueous KOH solutions for 0.5 hours, and the resulting nanoparticles are active electrocatalysts for water oxidation reaction (WOR) in alkaline solutions. The Co0.75 Fe0.25 Ox Hy NP, which are the most active electrocatalysts, have a layered double hydroxide (LDH) structure, with the average particle sizes about 16 nm. When using Ni foam as the substrate, the electrode with Co0.75 Fe0.25 Ox Hy NP as catalysts exhibited an overpotential of 284 mV for WOR in 1 M KOH at 10 mA cm −2 . The Tafel slope was 43 mV dec −1, and the TOF was 1.30 s −1 at 350 mV overpotential (loading Co + Fe = 0.133 mg cm −2 ). The Co0.75 Fe0.25 Ox Hy NP are robust toward long‐term galvanostatic test and showed less than 2% dissolution in 10 hours. Preliminary kinetic study suggests that the presence of Fe in Co1−z Fez Ox Hy NP alters the WOR mechanistic pathways. The increased number of electrochemically active sites endowed by the LDH structure and the electronic interactions between Co and Fe as suggested by XPS, both contribute to the enhanced WOR activity. Abstract : A simple co‐precipitation method was adopted to prepare a series of CoFe hydrous oxide nanoparticles in air at room temperature, with the most active nanoparticles exhibited an overpotential of 284 mV for water oxidation reaction in 1 M KOH at 10 mA cm −2 . The catalysts can be separated as powders and can be applied to various substrates with desired loadings. The origins for enhanced water oxidation activity caused by the presence of Fe in the catalysts were investigated.